Neuropathogenic role of adenylate kinase-1 in Abeta-mediated tau phosphorylation via AMPK and GSK3beta. - Park, H.; Kam, T.I.; Kim, Y.; Choi, H.; Gwon, Y.; Kim, C.; Koh, J.Y.; Jung, Y.K. (Human Molecular Genetics, 2012)
Abnormally hyperphosphorylated tau is often caused by tau kinases, such as GSK3? and Cdk5. Such occurrence leads to neurofibrillary tangle formation and neuronal degeneration in tauopathy, including Alzheimer's disease (AD). However, little is known about the signaling cascade underlying the pathologic phosphorylation of tau by A?(42). In this study, we show that adenylate kinase 1 (AK1) is a novel regulator of abnormal tau phosphorylation. AK1 expression is markedly increased in the brains of AD patients and AD model mice and is significantly induced by A?(42) in the primary neurons. Ectopic expression of AK1 alone augments the pathologic phosphorylation of tau at PHF1, CP13 and AT180 epitopes and enhances the formation of tau aggregates. Inversely, downregulation of AK1 alleviates A?(42)-induced hyperphosphorylation of tau. AK1 plays a role in A?(42)-induced impairment of AMPK activity and GSK3? activation in the primary neurons. Pharmacologic studies show that treatment with an AMPK inhibitor activates GSK3?, and a GSK3? inhibitor attenuates AK1-mediated tau phosphorylation. In a Drosophila model of human tauopathy, the retinal expression of human AK1 severely exacerbates rough eye phenotype and increases abnormal tau phosphorylation. Further, neural expression of AK1 reduces the lifespan of tau transgenic files. Taken together, these observations indicate that the neuronal expression of AK1 is induced by A?(42) to increase abnormal tau phosphorylation via AMPK-GSK3? and contributes to tau-mediated neurodegeneration, providing a new upstream modulator of GSK3? in the pathologic phosphorylation of tau.